PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2012 - Wehdawati; Fifi Swandari; Sufi Jikrillah (JWM (JURNAL WAWASAN MANAJEMEN), 2015)
This study aims to identify and analyze the influence of the number of commissioners, the proportion of independent board, the number of audit committee, the number of the board of directors, managerial ownership, institutional ownership as the independent variables, and the company size as the control variable either partially or simultaneously on the company’s financial performance, namely ROA and ROE as dependent variables in companies listed on the Stock Exchange from 2010 to2012. The method of sampling was done through purposive sampling method. The population of companies were the ones listed on the Stock Exchange from 2010 to 2012. The obtained samples were 91 companies, so that the amount of data used were as many as 273, but there are some outlier data that must be removed in order to meet the assumption of normality. Therefore, the amount of the final samples used in this study were 75 companies with the amount of data used were 194. The analytical tool used was multiple linear regression analysis, and to test the level of significance the F test and the t-test were used which were processed with SPSS 22. The results showed that the variable of the proportion of independent board significantly gave negative effects on ROA and ROE, while the variable of the number of commissioners, the number of board of directors, managerial ownership, institutional ownership and firm size did not affect the ROA and ROE. The variable of the number of the audit committee was not used in the analysis because the data had constant value.